Personal Branding di Media Sosial Tiktok - I Made Chandra Mandira; Kadek Diah Yulia Carey (MBIA, 2023)
This research finds out the personal branding President of Oriflame on social media tiktok seen from what does, what makes it different, and scores what to get when the public intertwines a connection with him. The study is conducted with a method qualitative with an approach to studies phenomenology for knowing more about somebody seen from professional experience in a manner that is aware and capable of giving meaning to every phenomenon experienced. Results findings in a study this is the President of Oriflame does not yet take advantage of social media tiktok with good because the target market no there, however, should as someone who has become a highlight and occupies ranking highest in Oriflame must permanently share content-related medium business on this with consistency across all social media, wrong only one tiktok as the most popular social media public moment this. Keywords: President of Oriflame, Personal Branding, Tiktok Abstrak Penelitian ini bertujuan untuk mengetahui personal branding President Oriflame di media sosial tiktok dilihat dari apa yang dilakukan, apa yang membuatnya berbeda dan nilai apa yang didapat ketika masyarakat menjalin hubungan dengannya. Penelitian ini dilakukan dengan metode kualitatif dengan pendekatan studi fenomenologi untuk bisa mengetahui lebih dalam tentang seseorang dilihat dari pengalaman yang dialami secara sadar dan mampu memberikan makna dari setiap fenomena yang dialami. Hasil temuan dalam penelitian ini adalah President Oriflame belum memanfaatkan media sosial tiktok dengan baik karena pasaran yang dituju bukan disana, namun semestinya sebagai orang yang sudah menjadi sorotan dan menduduki peringkat tertinggi di Oriflame harus tetap membagikan konten terkait bisnis yang sedang dijalani dengan konsisten di semua media sosial, salah satunya tiktok sebagai media sosial paling diminati masyarakat saat ini. Kata kunci: President Oriflame, Personal Branding, Tiktok